Laparoscopic splenectomy in children with sickle cell disease younger than 5 years old - Taha Alkhatrawi; Radi Elsherbini; Waheed Turkistani (SpringerOpen, 2020)
Abstract Background The purpose of this paper is to evaluate the feasibility, safety, efficacy, benefits, and outcome of elective laparoscopic splenectomy for children younger than 5 years with sickle cell disease (SCD) who needed splenectomy. We conducted a retrospective review for a prospective data on patients younger than 5 years with SCD requiring splenectomy from January 2007 to June 2019. Patients were evaluated with regard to patient demographics, operative time, presence of accessory spleens, blood loss, length of hospital stay, morbidity, mortality, and clinical outcome. Results A total of 71 patients younger than 5 years with SCD underwent laparoscopic splenectomy (LS) at our institution from January 2007 to June 2019. There were 28 boys and 43 girls. The age at LS is from 2 years to less than 5 years (mean 3.2 years). The mean operating time was 65 min. There was no conversion to open surgery; all the cases were successfully performed laparoscopically. Twelve patients (17%) underwent a concomitant cholecystectomy. The hospital stay ranged from 2 to 6 days (median, 3 days). The mean follow-up was 86 months (range, 17 to 161 months). Postoperative follow-up revealed no cases of overwhelming postsplenectomy sepsis infection (OPSI). Conclusion Laparoscopic splenectomy in young children less than 5 years of age with sickle cell disease is a safe and effective treatment. When patients are given preoperative vaccination and penicillin prophylaxis, OPSI rarely occurs.